DOES THE ECONOMIC VALUE OF THE PRAMBANAN TEMPLE REFLECT ITS HERITAGE VALUE? - Nabila Wahyu Mulia; Norma Ayu Elvina; Sahira Marisa Nuratri; Depri Depri (MESP–FEB UNS, 2024)
This study aims to estimate the economic value of the Prambanan Temple tourist attraction using the Travel Cost Method (TCM). The visitor willingness to pay for entrance tickets is used to reflect the economic value of the Prambanan Temple's cultural heritage, assessed with the Individual Travel Cost Method (ITCM) approach. The analysis utilizes Ordinary Least Squares (OLS) regression. The study included 186 respondents. Total visitor willingness to pay for the Prambanan Temple is Rp 10,747,976 (688.57), with an average visitor willingness to pay of Rp 57,753 (3.70) per visit. The current entrance ticket price is Rp 50,000 (3.22). This suggests that the value of the Prambanan Temple's cultural heritage to visitors is higher than the current ticket price. The consumer surplus generated by the 186 respondents is Rp 1,399,358 (89.65), with a consumer surplus per individual of Rp 7,492 (0.48).